Related factors to fear and stigma of COVID-19 - Lili Amaliah; Ernawati Umar; Ahmad Darajat; Ilma Fiddyanti (Intelektual Pustaka Media Utama, 2022)
Few studies have explored the fear and stigma of COVID-19 among the general Indonesian population. This study aimed to investigate the fear and stigma of COVID-19-related factors among the general population. A cross-sectional study was done in Banten, Indonesia, from Augustus to September 2020. Sample of the studywas recruited using convenience sampling. Multivariable linear regression model was used to analyze data. The majority of respondents were female (66.9%), with the mean age was 32.5 (SD=8.7). Fear of COVID-19 score was negatively associated with social support. Stigma towards COVID-19 score was negatively associated with higher education level, knowledge, social support. It positively associated with non-healthcare professional living in the city, confirmed COVID-19, suspected case, quarantine for close contact, and fear of COVID-19. The results indicated that the COVID-19 fear and stigma have been experienced by many of the general Indonesian community. Therefore, public health education and awareness-raising of the significance of public support are needed to remove the perceived stigma.